2018
DOI: 10.1002/sd.1873
|View full text |Cite
|
Sign up to set email alerts
|

Trade‐offs between sustainable tourism development goals: An analysis of Tibet (China)

Abstract: In the field of tourism development, decision-makers are often confronted with multiple goals regarding the tourism economy, environment and society. Taking Tibet (China) as a case study, the current paper proposes an innovative methodology for quantifying the trade-off between various tourism development goals, drawing on the Delphi method and goal programing. Our results indicate that Tibet's sustainable tourism development goals mainly consist of 10 subgoals and depend on nine decision-making variables. Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Tourism also has an important effect on social, political, and economic activities. In view of this, Zhang and Zhang (2019) indicated that achieving socio, economic, and environmental goals is equally important for the development of tourism sector. The sustainable tourism development is hoped in the longrun if prosperity of the people, community well-being, and resources efficiency are given greater priority (Dłużewska, 2019).…”
Section: Concluding Remarks and Implications For Tourism Developmentmentioning
confidence: 99%
“…Tourism also has an important effect on social, political, and economic activities. In view of this, Zhang and Zhang (2019) indicated that achieving socio, economic, and environmental goals is equally important for the development of tourism sector. The sustainable tourism development is hoped in the longrun if prosperity of the people, community well-being, and resources efficiency are given greater priority (Dłużewska, 2019).…”
Section: Concluding Remarks and Implications For Tourism Developmentmentioning
confidence: 99%
“…The area is rich in natural and cultural landscape resources, where the development conditions of mountain tourism are vastly superior and are of utmost importance and significance. The Western Sichuan Plateau Mountain Areas (WSPMA)are located in minority areas as a representative of the development of mountain tourism in Western China [2], where tourism is an essential development model for ethnic minority areas in Western Sichuan [55,56]. Due to this, we considered the WSPTA, as a typical mountain tourism research destination with multicultural and rich landscape resources, for our research study.…”
Section: Study Areamentioning
confidence: 99%
“…opment of mountain tourism in Western China [2], where tourism is an essential development model for ethnic minority areas in Western Sichuan [55,56]. Due to this, we considered the WSPTA, as a typical mountain tourism research destination with multicultural and rich landscape resources, for our research study.…”
Section: Data Collectionmentioning
confidence: 99%
“…Until recently, high-altitude travel was most concentrated in Nepal. Now, however, growing numbers of domestic tourists from India and China are visiting both sides of the Himalaya (Angmo and Dolma 2015;Zhang and Zhang 2019).…”
Section: The Contemporary Environmentmentioning
confidence: 99%